2021
DOI: 10.3390/ijerph18084223
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships between Safety Compliance, Safety Participation and Safety Outcomes: Considering the Moderating Role of Job Burnout

Abstract: Safety compliance (SC) and safety participation (SP), which are key factors predicting safety outcomes (e.g., accidents, injuries and near misses), are related but distinct. However, which component is more significant remains controversial. Job burnout is a typical occupational psychological syndrome of employees that impacts safety outcomes, but the role that it plays in the relationship between SC, SP and safety outcomes is ambiguous. To clarify these relationships, Chinese coal mine workers were sampled. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…However, future studies can evaluate more complex relationships between safety participation behaviors and stress reactions. For example, studies showed the moderating role of burnout on the relationship between safety participation and safety outcomes [ 56 ]. Moreover, studies may also expand such evidence by applying longitudinal research designs to analyze mutual relationships between emotional exhaustion and safety behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies can evaluate more complex relationships between safety participation behaviors and stress reactions. For example, studies showed the moderating role of burnout on the relationship between safety participation and safety outcomes [ 56 ]. Moreover, studies may also expand such evidence by applying longitudinal research designs to analyze mutual relationships between emotional exhaustion and safety behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This research is an addition to the extant body of literature (Curado and Santos, 2021; Mittal, 2016; Scuotto et al , 2022; Ladan et al , 2017a; Jena and Swain, 2021; Herman et al , 2013) that TL fosters JS and reduces JTI via JS in Thai a health-care setting. We add to the prior literature (Yang et al , 2021; Liu et al , 2021; Shkoler and Tziner, 2017; Leunissen et al , 2018; De Boeck et al , 2017) by studying moderating role of CBO between JS and JTI, and KH and JTI in Thai health-care perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of SP is voluntary, while SC belongs to in-role behaviour [44,45]. Several studies have recognised SC and SP as predictors of occupational accidents and injuries [46][47][48]. Wang et al [49] revealed the importance of SC and SP in accident prevention in construction projects.…”
Section: Literature Review 21 Safety Behaviourmentioning
confidence: 99%